The Medieval Economy of Salvation : Charity, Commerce, and the Rise of the Hospital - Davis, Adam Jeffrey, 1973- (Book collections on Project MUSE., 2019)
"Explores the connection between the medieval commercial economy and the rise of hospitals as new charitable institutions in the Latin West"--